Strategi Politik Dalam Pemilihan Kepala Desa Gondowangi Tahun 2018 - Ronald Zainul Muttaqin Ronald Zainul Muttaqin; Sakir; Fairuz Arta (Departemen Ilmu Pemerintahan Fisip Unhas, 2022)
This article examines the political strategies employed in the 2018 Village Head Election in Gondowangi Village, Magelang Regency. Political strategy plays an essential role in electoral contests because it influences candidate competitiveness and voter support (Schroder, 2009). This study aims to analyze the political strategies and political communication patterns implemented by the candidates during the election process. The research employed a qualitative case study approach using observations and interviews with campaign teams and community members. The findings reveal that the candidates utilized various political strategies, including personal branding, voter mobilization, campaign activities, and interpersonal political communication. Effective communication with community leaders and local organizations significantly contributed to increasing electoral support. The study concludes that political strategy and political communication are important determinants of success in village head elections, particularly in building public trust and consolidating voter support.